Information communication technologies for human services education and delivery concepts and cases - Martin, Jennifer, 1959-; Hawkins, Linette; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2010)
Information communication technologies in human services are of increasing interest and concern to health and welfare educators, managers, and practitioners due to their useful information management and teaching capabilities. This book significantly contributes to the growing area of ICT application in education and human service delivery. Containing expert international contributions, it showcases innovative practices, addresses ethical and logistic concerns, and provides relevant theoretical frameworks and the latest empirical research findings.
Social shaping of technologies for community development: redeployment of information communication technologies among the Kelabit in Bario of the Kelabit Highlands / Poline Bala -- Social policy and information communication technologies / Paul Henman -- Knowledge sharing online: for health promotion and community education: e-mavenism / Hyunjung Kim, Michael A. Stefanone -- Afterword / Dennis Perry.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on June 22, 2010).
Keywords: Human services -- Computer network resources; Social service -- Computer network resources; Social service education -- Computer network resources; Applications of case management software; Blended learning design; Designing e-learning environments; Educational and social benefits of social network sites; Groupwork concepts for online teaching; Human rights monitoring and advocacy; Human services education; Information communication technologies for human services; Knowledge sharing online; Multidisciplinary human services workforce; Social shaping of technologies; Sustaining community in a virtual world; Virtual situated learning environments; Electronic books